NYAMUK (DIPTERA:CULICIDAE) TAMAN NASIONAL BOGANINANI WARTABONE, SULAWESI UTARA: KERAGAMAN, STATUS DAN HABITATNYA - Awit - Suwito (ZOO INDONESIA, 2008)
Suwito, A. 2008. The Mosquito (Diptera: Culicidae) of Boganinani WartaboneNational Park, North Sulawesi: Diversity, Status and Habitat. Zoo Indonesia17(1):27-34. Mosquitoes need suitable habitats for the development of larvae. Larvaehabitats were identified and characterized at three locations: Mauk-Molotong River &Mainakum in Boganinani Wartabone National Park, and Mount Pakinya near PusianVillage out side from national park. Larvae were collected from bamboo stump, treeholes or puddle on the stones, while adults were collected using insect net and lighttrap especially in Mount Pakinya. Totally twenty two species of mosquitoes from sevengenera were identified morphologically. Species of Anopheles spp. and Culex spp.were the most dominant in Mount Pakinya. The conversion of forest becomes padifield and villages would rise new habitats of breeding sites, that finally would changethe distribution and composition of mosquitoes.